2015
DOI: 10.2131/jts.40.647
|View full text |Cite
|
Sign up to set email alerts
|

Modifying effects of 1,2-dichloropropane on N-nitrosobis(2-oxopropyl)amine-induced cholangiocarcinogenesis in male Syrian hamsters

Abstract: -Based on the findings of epidemiological studies in Japan that occupational exposure to 1,2-dichloropropane (1,2-DCP) was associated with increased cholangiocarcinomas, 1,2-DCP has recently been classified as being carcinogenic to humans (Group 1). However, the cholangiocarcinogenicity of 1,2-DCP has not been demonstrated experimentally, and it was negative for cholangiocarcinogenicity in rats and mice. The present study determined the effects of 1,2-DCP on N-nitrosobis(2-oxopropyl)amine (BOP)-induced cholang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 26 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…In 2013, the high incidence of bile duct cancer (cholangiocarcinoma) was first reported in workers at the offset color proof‐printing section of a printing company in Japan (Kumagai, Kurumatani, Arimoto, & Ichihara, ), which prompted more research about the carcinogenicity of 1,2‐DCP. Experimental studies revealed that gavage and inhalation of 1,2‐DCP caused bronchioloalveolar adenomas, carcinomas, nasal cavity tumors and Harderian gland adenomas in mice and rats (Gi et al, ; Kubo et al, ; Matsumoto, Umeda, Take, Nishizawa, & Fukushima, ; Toyoda, Takada, & Suzuki, ; Toyoda, Takada, & Suzuki, ). Based on the epidemiological data and toxicology studies on 1,2‐DCP, IARC reclassified 1,2‐DCP as a group 1 carcinogen (Benbrahim‐Tallaa et al, ; Kubo et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2013, the high incidence of bile duct cancer (cholangiocarcinoma) was first reported in workers at the offset color proof‐printing section of a printing company in Japan (Kumagai, Kurumatani, Arimoto, & Ichihara, ), which prompted more research about the carcinogenicity of 1,2‐DCP. Experimental studies revealed that gavage and inhalation of 1,2‐DCP caused bronchioloalveolar adenomas, carcinomas, nasal cavity tumors and Harderian gland adenomas in mice and rats (Gi et al, ; Kubo et al, ; Matsumoto, Umeda, Take, Nishizawa, & Fukushima, ; Toyoda, Takada, & Suzuki, ; Toyoda, Takada, & Suzuki, ). Based on the epidemiological data and toxicology studies on 1,2‐DCP, IARC reclassified 1,2‐DCP as a group 1 carcinogen (Benbrahim‐Tallaa et al, ; Kubo et al, ).…”
Section: Introductionmentioning
confidence: 99%